2014
DOI: 10.1093/jxb/eru269
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of plant physiology by glyphosate and its by-product aminomethylphosphonic acid: an overview

Abstract: It is generally claimed that glyphosate kills undesired plants by affecting the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme, disturbing the shikimate pathway. However, the mechanisms leading to plant death may also be related to secondary or indirect effects of glyphosate on plant physiology. Moreover, some plants can metabolize glyphosate to aminomethylphosphonic acid (AMPA) or be exposed to AMPA from different environmental matrices. AMPA is a recognized phytotoxin, and its co-occurrence with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
232
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(242 citation statements)
references
References 98 publications
3
232
2
5
Order By: Relevance
“…Increased phosphorous nutrition is known to protect plants from environmental stress (i.e., trace-elements contamination) through phosphorous stimulation of antioxidant systems, thus preventing oxidative tissue damage (Gomes et al, 2013(Gomes et al, , 2014b. Like trace-elements (Gomes et al, 2013(Gomes et al, , 2014b, glyphosate is known to induce oxidative stress in plants (as reviewed by Gomes et al, 2014a). Here, we demonstrated that glyphosate induced lipid peroxidation (malondialdehyde -MDA contents, from 29 to 52%) in willow roots (Fig.…”
Section: Mainmentioning
confidence: 54%
See 1 more Smart Citation
“…Increased phosphorous nutrition is known to protect plants from environmental stress (i.e., trace-elements contamination) through phosphorous stimulation of antioxidant systems, thus preventing oxidative tissue damage (Gomes et al, 2013(Gomes et al, , 2014b. Like trace-elements (Gomes et al, 2013(Gomes et al, , 2014b, glyphosate is known to induce oxidative stress in plants (as reviewed by Gomes et al, 2014a). Here, we demonstrated that glyphosate induced lipid peroxidation (malondialdehyde -MDA contents, from 29 to 52%) in willow roots (Fig.…”
Section: Mainmentioning
confidence: 54%
“…In this context, new GR plants could be developed by selecting those with membrane carriers having high specific affinities for P, assuring P nutrition with less glyphosate uptake (thus decreasing secondary glyphosate toxic effects on GR plants). However, in this case, the expected increased free glyphosate concentration might have detrimental effects on soil biological community (Correia and Moreira, 2010;Gomes et al, 2014a;Pham et al, 2015), and therefore, strategies to accelerate glyphosate's dissipation or biodegradation (e.g. by increasing soils microbial glyphosate degrader community) should be investigated for their efficiency and impacts on the environment.…”
Section: Mainmentioning
confidence: 99%
“…Other herbicides, such as glyphosate, indirectly affect by inhibiting the biosynthesis of carotenoids, chlorophyll, fatty acids, etc. (Olesen and Cedergreen, 2010;Gomes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Absorbed by the plant through the leaves, glyphosate acts on aromatic amino acid synthesis by competitive inhibition of the enzyme EPSPs (5-enolpyruvylshikimate-3-phosphate synthase), blocking the metabolic synthesis of phenylalanine, tyrosine and tryptophan (Forlani et al 2008). Some secondary effects have also been reported (Zobiole et al 2012;Serra et al 2013;Gomes et al 2014), such as the assimilation of Ca, Fe and Mn, which can be affected by the glyphosate complexation of these nutrients, inhibiting the translocation processes inside the plant (Senem Su et al 2009;Zobiole et al 2012). The increased oxidative stress caused by the inhibition of aromatic amino acid synthesis has been observed with greater concentrations of ascorbate and inositol (Serra et al 2013;Gomes et al 2014).…”
Section: Introductionmentioning
confidence: 99%